An Open Randomised Clinical Study to Evaluate the Combined Effect of Krishna Tila Kashayam and Shatapuspa Choornam in PCOS (International Journal of Ayurveda and Pharma Research, 2024)
PCOS has ovarian dysfunction along with hyperandrogenism and polycystic ovarian morphology. PCOS is a condition where involvement of Kapha dosha is present along with Vata dosha along with Rasa Dhatu, Medo dhatu and Arthava- the Upadhatu of Rasa is affected. Because of having the properties of Ushna virya, Kashaya Tiktha rasa, Arthava janana properties, Krishna Tila Kashayam and Shatapuspa choornam has been mentioned for the treatment of Arthava kshaya (anovulation and oligomenorrhea) in PCOS. The treatment is fully focused on Vata Kapha hara chikitsa and Arthava vardhaka. The drugs selected for the present study can be easily prepared and administered, cost effective. In this study, Tila kashayam along with Anupanam Gudam and Shatapuspa choornam along with Anupanam Madhu has been given and the results have been noted. In the present study, a total of 40 patients suffering from PCOS were selected from OPD and IPD of SJSACH. The thesis is widely focused on increasing the quantity of flow in amenorrhoea or oligomenorrhea cases, to check the size of the ovarian follicle before and after treatment and to check if there is any reduction in hair growth in hirsutism patients. There was a notable change seen in mild to moderate PCOS cases regarding the interval between 2 cycles, duration of flow between 2 cycles and quantity of flow between 2 cycles. There was a notable change seen in reduction of ovarian cyst volume before and after treatment. Hirsutism, BMI and waist circumference - there was no significant changes noted during these 3-month period.